Study of Antecedent of Customer Satisfaction and Loyalty for Kompas Klasika Jateng & DIY - Ratna, Maria Moniqua; Soesanto, Harry; Sukresna, I Made (Master of Management Diponegoro University, 2017)
The purpose of this research is to investigate the effect of core service quality, peripheral service quality, and corporate image on customer satisfaction and loyalty of advertiser of Kompas Klasika Jateng&DIY. Â Data were collected from 200 clients (advertisers) of Kompas Klasika Jateng&DIY using purposive sampling method, and the data processed using the AMOS software analysis technique Structural Equation Modelling (SEM) version 23.0. Â The research reveals there is a positive and significant correlation between peripheral service quality to the customer satisfaction (CR = 4,115) and to the customer loyalty (CR= 2,614); corporate image to the customer satisfaction (CR= 4,976) and to the customer loyalty (CR= 2,580). While, the correlation of the core service quality to the customer satisfaction and loyalty is have no significant impact (each shows that CR= 1,387 and CR= -0,412), so does the impact of customer satisfaction to the customer loyalty (CR= 0,997).Â Keyword: Core Service Quality, Peripheral Service Quality, Corporate Image, Customer Satisfaction, Customer Loyalty